THE ROLE OF COMPETENCY ON EMPLOYEE PERFORMANCE ACHIEVEMENT: A LIERATURE REVIEW - sumiyati; Arif Prabowo; Ahmad Anas (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2021)
The purpose of this study is to explain the theoretical framework about the role of training education as an increase in the performance of employees who have attended training education, as a driving force for employee performance to improve work supported by the work environment in each workplace with competency variables. This research uses the literature method. This research was conducted by searching for reference materials in the form of books, scientific journals, magazines, articles and research reports related to the research objectives. This study uses deductive and interpretive methods of data analysis. The results showed that education and training are a means of providing knowledge related to employees’ daily tasks, this knowledge can provide its own competencies for employee success in achieving better performance. The work environment is a support for fulfilling the completion of an employee’s duties. The creation of a working environment must be comfortable, supported by performance support facilities, and vice versa. Conducting training in a company is expected to have all the potential that employees have, so that employees can work better, with this the employee’s work performance will be better too. The work environment is not only a spatial arrangement with such a design by the company but also a kinship atmosphere, hereby intended to improve employee performance so that they are more enthusiastic, effective and efficient in carrying out their work. Employee competence plays a role in determining behavior and results. Competence is an attitude inherent in humans that allows someone to carry out an action or mental or physical work.